2019
DOI: 10.1002/jper.19-0142
|View full text |Cite
|
Sign up to set email alerts
|

Time analysis of alveolar ridge preservation using a combination of mineralized bone‐plug and dense‐polytetrafluoroethylene membrane: A histomorphometric study

Abstract: Background The objective of this study was to histologically evaluate and compare vital bone formation, residual graft particles, and fraction of connective tissue (CT)/other tissues between three different time points at 2‐month intervals after alveolar ridge preservation with a cancellous allograft and dense‒polytetrafluoroethylene (d‐PTFE) membrane. Methods Ridge preservation with a cancellous allograft and d‐PTFE membrane was performed at 49 extraction sockets (one per patient). Volunteers were assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…The wish of avoiding intraoral bone block harvesting and the risk of donor site morbidity of all patients could be met by the application of allogeneic cortical struts. The vast remodeling potential of allogeneic bone chips was recently demonstrated by Wen and colleagues 40 . They found 41% new bone in extraction sockets preserved with allogeneic granules after 4 months of healing.…”
Section: Discussionmentioning
confidence: 88%
“…The wish of avoiding intraoral bone block harvesting and the risk of donor site morbidity of all patients could be met by the application of allogeneic cortical struts. The vast remodeling potential of allogeneic bone chips was recently demonstrated by Wen and colleagues 40 . They found 41% new bone in extraction sockets preserved with allogeneic granules after 4 months of healing.…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, a recent study evaluating the outcomes of surgically treated peri‐implant defects, found that the morphology and pattern of bone loss at baseline significantly influenced the surgical results of both regenerative and resective procedures 49 . Considering the advantages of each of the mentioned variables on the outcomes of bone regeneration, 50–52 it is plausible that the higher DF, RDF and therefore the greater PD reduction could be attributable to any, or all of the aforementioned differences collectively.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, d-PTFE membranes allow volume stability and avoid ridge collapse while facilitating cellular adhesion to the membrane's surface, shielding bacterial invasion and forming a hermetic seal [40,41]. Phenotypic architectural conservation of the soft tissue is retained while assisting underlying socket healing, resulting in beneficial clinical outcomes [27,42,43]. Notably, no primary closure is required when using a d-PFTE membrane in ST3B and ST3C [44].…”
Section: Discussionmentioning
confidence: 99%